Mutual relations between sleep deprivation, sleep stealers and risk behaviours in adolescents - Paiva, Teresa (2016)
Objectives: The aim is to evaluate the mutual influences between sleep duration/sleep deprivation (SD) and the sleep stealers/adolescent risk behaviours. Methods: The national survey is a component of the Health Behaviour in School-Aged Children (HBSC) study, it is based on a school-based self-completed questionnaire; 3476 students were randomly selected from 139 randomly chosen Portuguese schools using as an unit the class, 53.8% were girls; 45.9% attended the 8th grade and 54.1% the 10th grade; the mean age was 14.9 years. The measured variables were: 1) gender and age; 2) sociodemographics; 3) sleep duration during the week and during weekends and computed SD; 4) screen time (computer use during the week and during the week end (PC use); watching TV and mobile phone use; 5) earlier sexual behaviour; 6) violent behaviours: fights, use of weapons; 7) use of tobacco, alcohol and drugs. The statistical analysis included Pearson chi-square tests and logistic regression. Results: Excessive use of mobile phone, of computer use during weekdays, and internet facilities; substance use; violence and earlier sexual relations had significantly higher prevalence in sleep deprived adolescents. By logistic regression only using PC during weekdays, tobacco, drugs and weapons were associated to SD, while SD was associated to PC use during weekdays, tobacco use and drugs’ use. Computer uses tend to be associated among themselves. Mobile phone is associated with computer practices and with alcohol and tobacco use. Tobacco is associated with most risk behaviours. Alcohol use is associated with other substance use, computer use and violent behaviours. Violence behaviours, earlier sex and drugs use tend to be associated among themselves.Conclusions: Sleep stealers use and risk behaviours are more prevalent in sleep deprived adolescents, but, in spite of significant individual associations, models of risk behaviours are still lacking.